Synthesis and characterization of one, two and three-dimensional Cu(I) polymers supported by bipyridylamide ligands. (1st November 2018) - Mugenzi, Clement; Powell, Douglas R.; Gerasimchuk, Nikolay N.; Yang, Lei
Graphical abstract: Four Cu(I) coordination polymers supported by bipyridylamide ligands were synthesized and characterized by X-ray crystallography, FT-IR, reflectance UV–Vis and TGA. Detailed structural analysis revealed how pyridyl nitrogen disposition and amide groups impact the dimensionality and self-penetration of the constructed coordination networks. Abstract: Reaction of bipyridylamide ligands N -(3-pyridyl)nicotinamide (3-pna), N -(4-pyridyl)nicotinamide (4-pna) and N -(4-pyridyl)isonicotinamide (4-pina) with Cu(I) salts afforded four coordination polymers. X-ray crystallography analysis showed one-, two- and three-dimensional networks. The correlation between the pyridyl nitrogen donor disposition and dimensionality of the structures was discussed. Reflectance UV–Vis and fluorescence spectroscopic methods were used to characterize the MLCT features of these complexes. Thermal stability of the coordination polymers under nitrogen was also investigated.